Elegância nos trópicos: as crônicas sociais de Gilberto Trompowsky nas revistas ilustradas nos anos de 1931 a 1957. - Silva, Roberta Paula Gomes (2018)
In this study, we analyze Gilberto Trompowsky’s work that was published in three illustrated magazines – Bazar, Ilustração Brasileira and O Cruzeiro. We aimed to understand the themes Trompowsky depicted in his chronicles, the elaborate representation of the bourgeois taste and what changed or remained by the time they were published, bearing in mind the magazines. From 1931 to 1932, Trompowsky was the artistic director at Bazar and drew several pictures for advertising and the magazine’s cover. Our hypothesis is that it was this magazine that aroused Trompowsky interest in social chronicles, which continued in Ilustração Brasileira, in 1937, by means of his monthly collaboration with the “Mundanismo” section under the pseudonym G. de A. until 1941. Finally, in O Cruzeiro during the 1940’s and 1950’s, he collaborated with the “Mundanismo” section, as well as with “Esporte e Elegância” and “O Nome da Semana” sections. In those social chronicles, he wrote about parties, such as dinner parties, weddings, birthday parties, artistic and cultural events and political celebrations held by Rio de Janeiro elites. The chronicles, with their words and images, made it possible to create a historical version of Trompowsky and his group, taking account of their ways of being, doing and behaving, as well as their economic, social and political position.